Economic education and science at the Belarusian State University (to the 100th anniversary of the university) - Kovalev, Mikhail M.; Koroleva, Anna A. (Journal of the Belarusian State University. Economics, 2021)
The article studies the history of the formation of economic education and science at the Belarusian State University until its centenary. The contribution of university scientists to the development of Belarusian economics is highlighted, as well as their contribution to the economic policy and practice of the Republic of Belarus.
Keywords: history of economics; history of the Belarusian State University; outstanding scientists-economists